Ensino a distância sobre o uso racional de antimicrobianos e prevenção da resistência microbiana na graduação médica: uma experiência inovadora - Laks, Michel [UNIFESP] (2016)
Objectives: To analyse the impact on knowledge improvement in antibiotic use and bacterial drug resistance using a web-based distance learning methodology to undergraduate medical students, and to analyse the perceptions of the students about this methodology. Method: An educational intervention study was designed in Hospital São Paulo, teaching hospital of Universidade Federal de São Paulo, 655 beds, public and tertiary care center. A free of charge web-distance course was applied to fifth-grade medical students for seven years, using Moodle platform. The issue was antimicrobial stewardship and prevention of bacterial resistance. The course last 100 hours of activities, with five theoretical modules, exercises and simulations. The students were tutored in their on-line activities, and there was a live class for discussions during the period of the course. Additionally, they answered two live evaluations (pre and post-tests) each year. Results: 606 undergraduate medical students finished the entire course, from 2008 to 2014, 74,45% of the total who applied to participate. The mean grade of the post-test was significantly higher in relation to the mean of pre-test in all years analysed (p <0,001). There was a higher percentage of approved students at pre-test that had the last update in the theme course less than a year, when compared with those with more than a year (p=0,004). It was observed a directly proportional relationship between dedication (in hours) and quality of participation, and this situation reflects also on the final mean (p=0,009) and on the percentage of approved students (p=0,028). The participants were beginners in web-based courses (67,4%), and 100,0% considered their knowledge regular or insufficient before the course, affirming that the theme is very important or important to be discussed during medical training. 50,6% of the students spent from 10 to 20 hours of dedication to the course; this dedication was considered “regular” by 50% of participants and “sufficient” by 32,3%. Even with this dedication 70,5% considered they learned “very much” or “above the expectations” about the theme, and that they would dedicate more time if they had it. Conclusion: The employment of a virtual platform was an interesting option to teaching and learning in infection control and anti-infective agents, with significant knowledge improvement, and should be considered as an activity to undergraduate medical students in the final period of their training. Additionally, we recommend to stimulate the involvement of the students in this modality of teaching, to improve their achievement and satisfaction.